Mitotic cells can repair DNA double-strand breaks via a homology-directed pathway. (3rd October 2020) - Sakamoto, Yuki; Kokuta, Tetsuya; Teshigahara, Ai; Iijima, Kenta; Kitao, Hiroyuki; Takata, Minoru; Tauchi, Hiroshi
Abstract: The choice of repair pathways of DNA double-strand breaks (DSBs) is dependent upon the cell cycle phases. While homologous recombination repair (HRR) is active between the S and G2 phases, its involvement in mitotic DSB repair has not been examined in detail. In the present study, we developed a new reporter assay system to detect homology-directed repair (HDR), a major pathway used for HRR, in combination with an inducible DSB-generation system. As expected, the maximal HDR activity was observed in the late S phase, along with minimal activity in the G1 phase and at the G1/S boundary. Surprisingly, significant HDR activity was observed in M phase, and the repair efficiency was similar to that observed in late S phase. HDR was also confirmed in metaphase cells collected with continuous colcemid exposure. ChIP assays revealed the recruitment of RAD51 to the vicinity of DSBs in M phase. In addition, the ChIP assay for gamma-H2AX and phosphorylated DNA-PKcs indicated that a part of M-phase cells with DSBs could proceed into the next G1 phase. These results provide evidence showing that a portion of mitotic cell DSBs are undoubtedly repaired through action of the HDR repair pathway.